Late Cenomanian ostracod faunas from the area south of Ain Sukhna, western side of the Gulf of Suez, Egypt - Boukhary, Mohamed (Array, 2009)
Summary: Ostracod faunas from an exposure of the Cenomanian Galala Formation in the area south of Ain Sukhna on the western side of the Gulf of Suez have yielded 11 species belonging to 10 genera. The recorded speciesare have been taxonomically described, discussed where required, and illustrated. The ostracod assemblage is characteristic for the late Cenomanian. It is composed of taxa of a typical marine shelf setting. The majority of the recorded species have a vastly extended geographic distribution in the areas along the southern shores of Tethys, indicating the absence of significant geographic barriers along this stretch during the late Cenomanian